Very high‐power short‐duration catheter ablation for treatment of cardiac arrhythmias: Insights from the FAST and FURIOUS study series - Heeger, Christian‐H.; Kuck, Karl‐Heinz; Tilz, Roland R. (Journal of cardiovascular electrophysiology, 2024)
The QDOT MICRO™ Catheter is a novel open‐irrigated contact force‐sensing radiofrequency ablation catheter. It offers very high‐power short‐duration (vHPSD) ablation with 90 W for 4 s to improve safety and efficacy of catheter ablation procedures. Although the QDOT MICRO™ Catheter was mainly designed for pulmonary vein isolation (PVI) its versatility to treat atrial fibrillation (AF) and other types of arrhythmias was recently evaluated by the FAST and FURIOUS study series and other studies and will be presented in this article. Available study and registry data as well as case reports concerning utilization of the QDOT MICRO™ Catheter for the treatment of cardiac arrhythmias including AF, focal and macroreentry atrial tachycardia, typical atrial flutter by cavotricuspid isthmus block, premature ventricular contractions, and accessory pathways were reviewed and summarized. In summary, the QDOT MICRO™ Catheter showed safety and efficacy for PVI and is able to treat also other types of arrhythmias as is was recently evaluated by case reports and the FAST and FURIOUS studies.